Promotive Effects in a-Monochloropropionic Acid Catalytic Synthesis with Propionic Anhydride - Xue*, Jianwei; Qi, Beibei; Wen, Xiaoguang; Wang, Yingying; Lv, Zhiping; Li, Fuxiang (Asian Journal of Chemistry, 2014)
Selective a-chlorination of propionic acid to synthesize a-monochloropropionic acid was investigated in a laboratory-scale at 130 ºC at atmospheric total pressure and in the presence of propionic anhydride as catalyst. Sulfuric acid and common Lewis acid were selected as promotive catalysts considering that the acid-catalyzed enolization is the rate determining step in the chlorination reaction of this experiment, also the reaction selectivity and activity were discussed in the presence of promotive catalysts. The studies revealed that the ferric chloride and sulfuric acid all have prominent promotive effects. Typically the amount of a-monochloropropionic acid can reach 96.14 % when 0.07 g of ferric chloride was added. Furthermore, our results demonstrated that the reaction selectivity and activity were dramatically enhanced after introducing Lewis acid as promotive catalysts.